Grounding Innovative Promotion of Literacy in Local Funds of Knowledge - Serpell, Robert (Papers in Education and Development, 2018)
Literacy can be understood as a cultural practice comparable to other cultural practices such as story-telling, song and dance. In that theoretical framework, the process of individual literacy learning involves the appropriation of constructs and rules that inform recurrent cultural activities. The sociolinguistic character of the Zambian society includes both societal linguistic diversity and individual multilingualism. Within this context, an innovative application of instructional technology to initial literacy learning was launched in Zambia, under the auspices of the Centre for Promotion of Literacy in Sub-Saharan Africa (CAPOLSA). Evaluation of its local effectiveness has included field-testing of an interactive digital letter-sound correspondence game on various platforms, teacher orientation, composition and distribution of child-friendly texts in several Bantu languages. Ramifications of the programme include the challenge of orthographic harmonization. The paper highlights the importance of integrating new technology with indigenous cultural resources in the designing of appropriate, effective and sustainable educational practices in Africa. Key words: cultural practices, multilingualism, primary schooling, initial literacy learning, Zambia